(untitled) (Revista de Investigaciones Universidad del Quindío, 2021)
The situation of the covid-19 pandemic has meant job losses in Latin America, mainly among the female gender. Faced with this delicate situation, businesses have re-emerged as an alternative to improve the quality of personal and family life. This is the case of the New Internet Business Entrepreneurs (“Nenis”), whose insertion has made it possible to satisfy basic needs -and other kinds-, achieve economic independence, personal improvement and empowerment, among other aspects identified in interviews and questionnaires applied to various sales groups of this nature in Mexico, since their own entrepreneurship allows them self-employment to work freely without depending on bosses or the requirement of working hours and dedicate themselves to taking care of their home, organizing the production and / or distribution of their goods in schedules at convenience, using basic but effective marketing strategies in social networks, which have become great allies of the "Nenis" to bring their products to consumers and make sales, thereby achieving a relevant inclusion in the economic sphere, social and marketing of your locality. Thus, with their actions of strength and resilience, they are an essential part of the economic reactivation during the current health emergency in the country.